2021
DOI: 10.3390/ani11113280
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antibiotic Therapies on Resistance Genes Dynamic and Composition of the Animal Gut Microbiota

Abstract: Antibiotics are major disruptors of the gastrointestinal microbiota, depleting bacterial species beneficial for the host health and favoring the emergence of potential pathogens. Furthermore, the intestine is a reactor of antibiotic resistance emergence, and the presence of antibiotics exacerbates the selection of resistant bacteria that can disseminate in the environment and propagate to further hosts. We reviewed studies analyzing the effect of antibiotics on the intestinal microbiota and antibiotic resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 126 publications
3
1
0
Order By: Relevance
“…We observed that the microbiome diversity of treated cattle was significantly disturbed in the short term, increasing ARGs conferring resistance to tetracyclines compared to control animals without exposure to OTC. This finding is consistent with previous studies that reported the perturbation of the gut microbiome following antibiotic treatment within a few days after antibiotic exposure [ 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…We observed that the microbiome diversity of treated cattle was significantly disturbed in the short term, increasing ARGs conferring resistance to tetracyclines compared to control animals without exposure to OTC. This finding is consistent with previous studies that reported the perturbation of the gut microbiome following antibiotic treatment within a few days after antibiotic exposure [ 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Generally, in all animals, irrespective of the type of antimicrobial administered, a decrease in species richness and alpha-diversity is observed [ 45 ], as was also the case in our study. The most profound effects of TMS on the intestinal microbiota were observed immediately after treatment, which is in line with previous reports that also demonstrated a rapid, significant decrease in alpha-diversity [ 5 , 35 , 46 ].…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, we did not observe a significant effect of hospitalisation without treatment on microbiota composition, but this might result from the small number of animals making it difficult to observe subtle changes. To our knowledge, no next-generation sequencing studies have been performed on horses to evaluate Generally, in all animals, irrespective of the type of antimicrobial administered, a decrease in species richness and alpha-diversity is observed [45], as was also the case in our study. The most profound effects of TMS on the intestinal microbiota were observed immediately after treatment, which is in line with previous reports that also demonstrated a rapid, significant decrease in alpha-diversity [5,35,46].…”
Section: Discussionsupporting
confidence: 76%
“…It is worth noting that the microbiota can be influenced by many factors, such as species, age, sex, breed, diet, surgery, and antibiotic interventions [17,19,46,47,[108][109][110][111]. These factors should be considered when evaluating the in vivo efficacy of probiotics, given that probiotics interact with the gut microbiota.…”
Section: Future Directionsmentioning
confidence: 99%